Rekayasa Bahasa dan Konstruksi Politik â€œPersatuan-Kesatuanâ€ dalam Wacana â€œNegara Kesatuan Republik Indonesiaâ€ - Suwignyo, Agus (Sekolah Pascasarjana UGM, 2020)
The formation of the Indonesian nation-state is inseparable from linguistic engineering. This includes phrases that transformed their lexical meaning to become a binding political concession produced by Indonesian political leaders in the 1940s and 1950s. The official name of the Indonesian state â€œThe Unitary State of the Republic of Indonesiaâ€ is the result of this political concession in the statecraft of Indonesia. This article aims to examine the meanings of the â€œunity and unitaryâ€ phrases in the imagined form of Indonesian nation-state. Why was â€œunity and unitaryâ€ an effective political tool for the shaping of the imagination of â€œIndonesiaâ€? Linguists and historians would these choices of words as a reflection of the power of language in the creation of facts. Language can transform a lexical fact into a material one. It is therefore essential to understand how did the phrase â€œunity and unitaryâ€ transform from a lexical to a political meaning in the context of Indonesian history? This article is based on literary analyses of official relevant documents, including the assembly proceeding of the Council for the Investigation of the Preparation for Indonesian Independence (Badan Penyelidik Usaha-usaha Persiapan Kemerdekaan Indonesia, BPUPKI) of August 1945, and the so-called Principal Guidelines for State Development (Garis-Garis Besar Haluan Negara, GBHN) of the New Order. It argues that the â€œunity and unitaryâ€ phrase represents a negotiation of diverse political elements which then shaped the crafting of Indonesian nation-state. The changes in the contexts in which the phrase was used show a changing association between the lexical and ideological meanings of the phrase. While these changes worked towards institutionalizing the Indonesian state, this article concludes that they also submerged the peopleâ€™s discontents. The phrase â€œunity and unitaryâ€ reflected the making of peopleâ€™s uniformity to a large extent.Â